Strategi Penguatan Pendidikan Karakter Pada Perguruan Tinggi - Ajeng Wulansari; Siti Munawaro; Musbar Ibrahim; Jedithjah Naapia Tamedi Papia; Syafruddin Syafruddin; Anggitya Alfiansari (Departement of Mathematics Education, 2023)
The challenges of education in this millennial era, especially in Indonesia, do not only refer to the classic problems of equalization and fulfillment of access, infrastructure and education financing, but also talk about the quality of graduates who must have qualified intellect in their fields while having high morality. Seeing these conditions, the availability of human resources with character is a very important need. This is done to prepare for global challenges and the nation's competitiveness, universities must be able to prepare a generation that has the ability and good character, thus the strategy of strengthening character education in learning carried out in lectures requires an integrated plan. The implementation of character education along with its monitoring and evaluation must also be prepared as optimally as possible. the concept of character education programmatically with a strategy that is mupuni such as the strategy of moral knowing, moral knowing, moral modeling, moral feeling ang loving, moral acting, punishment, habituation.